Acute Fatty Liver of Pregnancy - Hin Hin Ko; Eric Yoshida (Canadian Journal of Gastroenterology)
Acute fatty liver of pregnancy (AFLP) is a rare, potentially fatal complication that occurs in the third trimester or early postpartum period. Although the exact pathogenesis is unknown, this disease has been linked to an abnormality in fetal fatty acid metabolism. Early diagnosis of AFLP sometimes can be difficult because it shares features with other common conditions such as pre-eclampsia, viral hepatitis and cholestasis of pregnancy. However, a careful history and physical examination, in conjunction with compatible laboratory and imaging results, are often sufficient to make the diagnosis, and liver biopsy is rarely indicated. Supportive care and expeditious delivery are essential to optimal maternal-fetal outcomes and remain as the mainstay treatment for AFLP.